Gender and Anticommunism in Children’s Social Protection in Postwar Greece: The Role of Royal Foundations - Avdela, Efi; Lampropoulou, Dimitra (Historein, 2024)
The article analyses the welfare activities provided by the Greek royal foundations in the period from their establishment in 1947 until 1968, focusing on their interventions concerning children and youth and their evolution over time. Placing the royal foundations’ activities in the Cold War and post-Civil War context, it argues that the intertwined state, parastatal and private initiatives, among which they had a hegemonic role, constituted the idiosyncratic Greek welfare state of the period, whose workings can be better grasped through the perspective of the mixed economy of welfare. Based on archival research, it highlights the gendered character of this specific version of welfare state-cum-mixed economy of welfare, and show that it was highly conservative, patriarchal and normative, based on ideological, political, class and gender exclusions. It depended on gendered massive voluntary action, especially women’s voluntary or low-paid work and elite women’s empowering activities.